Tectonophysical conditions of late stages of evolution in the middle part of Transcarpathian deep fault - Shevchuk, V.; Vasilenko, A. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2015)
There is a problem of the mechanism of Neogene magmatism appearance in Transcarpathia within  tectonic evolution of the Carpathian-Pannonian region. In consideration of general submeridional compression the new kinematic and dynamic scheme of Neogene tectonic and magmatic activation associates magmatism with formation of the shear-zone with right-shift structural paragenesis in the Transcarpathian trough area. According to the scheme the sources of volcanic eruptions were concentrated within the bounds of tension gashes that progressed during the shear-zone impulse evolution. Due to outcrop features of the region the structural argumentation of proposed scheme is effective only in north-eastern border of the shear-zone, on the Transcarpathian deep fault territory, where fault parageneses of different ranks are mapped. Detailed studies carried out within the middle part of the Transcarpathian deep fault allowed to show the jet structure of the central zone of the fault and the intense crushing and exfoliation of flysch formation that took place before volcanism as well as post-volcanic fissure formation. Three stages of fissure formation were marked out and the tectonophysical analysis of their paragenesis shows right-side shift type of local stress fields. The modification of the axes orientation of main normal stresses is explained by consistent implementation of the trans-pressure scheme, the simple shear scheme and the trans-tension scheme. The volcanic rocks, which cover tectonic rocks of the Transcarpathian deep fault seam zone, contain the sporadically shown up fault structures that are the evidence of lateral as well as sub-vertical displacement.